Toll-like receptor 7-driven lupus autoimmunity induces hypertension and vascular alterations in mice. Issue 7 (July 2020) - Robles-Vera, Iñaki; Visitación, Néstor De La; Toral, Marta; Sánchez, Manuel; Gómez-Guzmán, Manuel; O'valle, Francisco; Jiménez, Rosario; Duarte, Juan; Romero, Miguel
Abstract : Objective: To investigate whether toll-like receptor 7 (TLR7) activation induces an increase in blood pressure and vascular damage in wild-type mice treated with the TLR7 agonist imiquimod (IMQ). Methods: Female BALB/c mice (7–9 week old) were randomly assigned to two experimental groups: an untreated control group and a group treated topically with IMQ (IMQ-treated) for 4 or 8 weeks. A group of IMQ-treated mice that take a combination of the antioxidants tempol and apocynin, and another treated IL-17-neutralizing antibody were also performed. Results: TLR7 activation gradually increased blood pressure, associated with elevated plasma levels of anti-dsDNA autoantibodies, splenomegaly, hepatomegaly, and severe expansion of splenic immune cells with an imbalance between proinflammatory T cells and regulatory T cells. TLR7 activation induced a marked vascular remodeling in mesenteric arteries characterized by an increased media–lumen ratio (≈40%), and an impaired endothelium-dependent vasorelaxation in aortas from wild-type mice after 8 weeks of treatment. In addition, an increased ROS production, as a result of the upregulation of NADPH oxidase subunits, and an enhanced vascular inflammation were found in aortas from IMQ-treated mice. These functional and structural vascular alterations induced by IMQ were improved by antioxidant treatment. Anti-IL-17 treatment reduced blood pressure and improved endothelial dysfunction in IMQ-treated mice. Conclusion: Our results demonstrate that TLR7 activation induces the development of hypertension and vascular damage in BALB/c mice, and further underscore the increased vascular inflammation and oxidative stress, mediated in part by IL-17, as key factors contributing to cardiovascular complications in this TLR7-driven lupus autoimmunity model. Abstract : Supplemental Digital Content is available in the text